2013
DOI: 10.1002/jbmr.1878
|View full text |Cite
|
Sign up to set email alerts
|

The association between fracture site and obesity in men: A population-Based cohort study

Abstract: A site-dependent association between obesity and fracture has been reported in postmenopausal women. In this study we investigated the relationship between body mass index (BMI) and fracture at different skeletal sites in older men (≥65 years). We carried out a population-based cohort study using data from the Sistema d'Informació per al Desenvolupament de l'Investigació en Atenció Primària (SIDIAP(Q) ) database. SIDIAP(Q) contains the primary care and hospital admission computerized medical records of >1300 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
76
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 34 publications
8
76
1
4
Order By: Relevance
“…In men, it has been reported that multiple rib fractures are associated with obesity. In a population based-study in Spain, analysing 139,419 men aged 65 years or over, hip fractures in obese individuals were significantly less common than in non-obese men (11). These data are in contrast to those of Nielson and cols., who found an increased incidence of hip fracture in men after adjustment for BMD (16).…”
Section: Site Of Fracturementioning
confidence: 70%
See 2 more Smart Citations
“…In men, it has been reported that multiple rib fractures are associated with obesity. In a population based-study in Spain, analysing 139,419 men aged 65 years or over, hip fractures in obese individuals were significantly less common than in non-obese men (11). These data are in contrast to those of Nielson and cols., who found an increased incidence of hip fracture in men after adjustment for BMD (16).…”
Section: Site Of Fracturementioning
confidence: 70%
“…Several studies have demonstrated that the relationship between BMI and fracture is site-specific (8,11,12,14,16,21,22). While obesity is protective against hip fracture in women, it is associated with higher risk of fractures at some other sites.…”
Section: Site Of Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…Inverse correlation between E2 levels, LBMD, and HBMD (p < 0.001, r(2) = −0.20; p < 0.001, r(2) = −0.19) Yang et al [2013] 1126 (360 men and 766 women), >50 years Lower abdominal fat was significantly associated with a higher fracture risk in women. There was no statistically significant association between aFM and fracture risk (HR 1.15; 95% CI 0.58-2.25) in men Greco et al [2013] 340 obese women Trunk fat negatively correlates with BMD at lumbar spine and femoral neck independently from vitamin D levels Premaor et al [2013] 139,419 old men Multiple rib fractures were more frequent in overweight (RR 3.42; 95% CI 1.03-11.37) and obese (RR 3.96; 95% CI 1.16-13.52) old men. Obesity was associated with a reduced risk of clinical spine, hip, pelvis, and wrist or forearm fracture and increased risk of multiple rib fractures when compared with normal weight or underweight men Watts [2014] 60,393 obese women aged ⩾ 55 years…”
Section: Studymentioning
confidence: 89%
“…Obesity is responsible for a high incidence of fall mainly because an obese subject is less well able to protect itself against a fall [22][23][24] . There are several studies that support that the site of fracture is depended on BMI (body mass index) [25][26][27][28][29][30] . In Global Longitudinal Study of Osteoporosis in Women (GLOW) was found that obesity, in contrast to widespread belief, is not protective against fracture, but also responsible for certain fractures, mainly in the ankle and upper leg.…”
Section: Obesity and Site Of Fracturementioning
confidence: 99%